Validation of a new handheld device for measuring resting metabolic rate and oxygen consumption in children - Nieman, D. C.; Austin, M. D.; Chilcote, S. M.; Benezra, L. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The purpose of this study was to assess the validity and reliability of the MedGem device to measure resting metabolic rate (RMR) in children. Subjects included 59 children (29 boys, 30 girls; mean age, 11.0 +/- 0.2 y). Subjects were given 4 RMR tests during 1 test session, cconsisting of 2 Douglas bag and 2 MedGem tests, in random counterbalanced order. No significant differences were found between Douglas bag and MedGem systems for oxygen consumption (209 +/- 5 and 213 +/- 5 mL/min, respectively, P = 0.106, r = 0.911, mean +/- standard deviation absolute difference 3.72 +/- 17.40 mL/min) or RMR (1460 +/- 39 and 1477 +/- 35 kcal/d, P = 0.286, r = 0.909, mean +/- standard deviation absolute difference 17.4 +/- 124 kcal/d). Standard error of estimates for oxygen consumption and RMR were 17.4 mL/min and 124 kcal/d, respectively. In conclusion, these data indicate that the MedGem is a reliable and valid system for measuring oxygen consumption and RMR in children.